2011
DOI: 10.1099/mic.0.044834-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of Alteromonas macleodii and Thiocapsa roseopersicina [NiFe] hydrogenases in Escherichia coli

Abstract: HynSL from Alteromonas macleodii 'deep ecotype' (AltDE) is an oxygen-tolerant and thermostable [NiFe] hydrogenase. Its two structural genes (hynSL), encoding small and large hydrogenase subunits, are surrounded by eight genes (hynD, hupH and hypCABDFE ) predicted to encode accessory proteins involved in maturation of the hydrogenase. A 13 kb fragment containing the ten structural and accessory genes along with three additional adjacent genes (orf2, cyt and orf1) was cloned into an IPTG-inducible expression vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…Heterologous expression of the A. macleodii hydrogenase has been previously reported in both E. coli [15] and the cyanobacterium S. elongatus [16]. These reports address general issues of aerobic expression of the A. macleodii hydrogenase, as in both these reports, aerobic handling was used throughout, established as safe in the original report on the enzyme [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterologous expression of the A. macleodii hydrogenase has been previously reported in both E. coli [15] and the cyanobacterium S. elongatus [16]. These reports address general issues of aerobic expression of the A. macleodii hydrogenase, as in both these reports, aerobic handling was used throughout, established as safe in the original report on the enzyme [14].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, because A. macleodii hydrogenase can be expressed as active enzyme in both E. coli [15] and in the photoautotrophic cyanobacterium S. elongatus [16], our strategy moving forward is to use expression in E. coli as a preliminary model system to rapidly generate and test promising modifications of the enzyme prior to experimentation in S. elongatus , which has a longer turnaround time for genetic manipulations. The H230C/P285C enzyme demonstrated the same qualitative performance over the wild type enzyme in extracts prepared from both S. elongatus and E. coli , validating this strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, the authors cloned a 13 kb fragment including the A. macleodii structural genes ( hynSL ) and 11 adjacent hypothetical accessory genes in an IPTG-inducible expression vector. The vector was transformed into an Escherichia coli ( E. coli ) mutant strain lacking its native hydrogenases [100]. Upon induction, HynSL from A. macleodii expressed in E. coli and was active, as determined by the in vitro hydrogen evolution assays.…”
Section: Key Advances In Cyanobacterial Researchmentioning
confidence: 99%
“…Upon induction, HynSL from A. macleodii expressed in E. coli and was active, as determined by the in vitro hydrogen evolution assays. The HynSL from A. macleodii shares about 60% identity to the HynSL from T. roseopersicina [100]. The authors also showed successful complementation of the T. roseopersicina structural gene with the accessory gene cluster from A. macleodii .…”
Section: Key Advances In Cyanobacterial Researchmentioning
confidence: 99%